Influence of post-harvest treatment with SmartFresh preparation on the preservation of plum fruit quality - T. G. Prichko; M. G. Germanova (Новые технологии, 2018)
Storability of plum fruits stipulated by varietal peculiarities have been studied. It’s been determined that treatment with SmartFresh is effective for a short-term storage of plum fruits of the varieties of Stanley, Fortuna and early Kabardin in the ordinary atmosphere and ensures preservation of commercial qualities (freshness, juiciness, hardness, turgor of pulp) and high biological value. The yield of standard fruits after 1 month of storage is more than 90% due to treatment with SmartFresh, natural weight loss is 1.3-1.8 times less, nutritional and biological value is 8-15% higher than the control one.